Phytoplankton in relation to water quality of Tanguar Haor ecosystem, Bangladesh: 2. Watch tower station (Dhaka University Journal of Biological Sciences, 2020)
Phytoplankton biomass in relation to some environmental and nutritional parameters at Watch Tower Station of Tanguar and Rauar Station has been studied. Since the Haor is a Ramsar Site, it is a globally important aquatic ecosystem. In the present investigation, the structure of the phytoplankton and the water quality factors were worked out and the data were compared Rauar Station with having the same ecosystem. Though weaker, a difference among alkalinity, total dissolved solids (TDS), conductivity, dissolved oxygen (DO), Secchi disc transparency, soluble reactive phosphorous (SRP), soluble reactive silicate (SRS), NO3-N, NH4+, chlorophyll-a and phytoplankton population density was found between the Watch Tower and the Rauar Station of Tanguar Haor. The mean values of the aforsaid parameters were found to some extent higher in the Watch Tower Station. The Watch Tower Station was deeper and perennial, where the depth of water varied from 3.0 - 9.5 m annually with a mean of 6.72 m. In the studied station, air and water temperature varied from 22.6 - 30.6 and 22.7 - 30.3°C, respectively. Water transparency ranged from 2.08 - 3.0 m. From December to March the pH remained 8.1-9.7 and alkalinity from 0.73 - 1.35 meq/l. However, from April to September these two parameters ranged from 7.5 - 7.7 and 0.33 - 1.35 meq/l, respectively. Dissolved oxygen (DO) and free CO2 concentration ranged from 2.5 - 6.09 and 0.084 - 0.087 mg/l, respectively. During April to September the Chlorophyll-a value ranged from 5.5 - 7.5 μg/l while the range of SRP was 24.23 - 30.05 μg/l during the same period. At the latter part of the study year i.e., during the dry period (December to March) those two parameters were relatively low in concentration. In April a high concentration of NH4+ (1380 μg/l) was reported from the haor, at other times this parameter ranged from 690 - 820 μg/l. The NO3-N ranged from 0.25 - 0.75 mg/l. High density of phytoplankton population (2690 ind./l) was reported at the time of high concentration of SRP (30.05 μg/l ) of the haor water. The chlorophyll-a value (7.5 μg/l) was also highest at that time. So, it could be said that SRP concentration in Tanguar haor has been playing a vital role in regulating the standing crop of phytoplankton. To find the variation on a spatial scale, the data of the present investigation were compared with another study station of the haor namely, Rauar Station. No significant difference was observed among the concentrations of different parameters. However, a slight increasing trend in the concentrations of DO, alkalinity, SRP, NO3-N, SRS, NH4+ and total phytoplankton density was observed in the Watch Tower Station compared to Rauar Station. Watch Tower Station is also relatively deeper with an improved light climate as it had been revealed by the mean value of the Secchi depth. The water quality of Tanguar Haor has been classified as mesotrophic.Dhaka Univ. J. Biol. Sci. 29(1): 9-18, 2020 (January)